Subjective objectivity: The effect of accounting competencies, financial literacy, perceptive considerations, personality traits, and subjective stock market factors on the investment behavior as mediated by investment intention in the Philippine Stock Exchange among certified public accountants - Mendoza, Genevieve Krissle Bravo (Animo Repository, 2021)
Accounting is vital in the field of finance; it is the language in the world of business. It allows how to make sense of the numbers arrived at and give a much more specific insight into what those numbers represent in reality, rather than just seeing them as a set of objective ratios. There are fields within the field that delve deeper into similar activities that are done in investing, but with different objectives, intents, and actions. Investments ensure present and future long-term financial security, thus can provide financial security and income. The decision to invest depends on knowledge, motivational factors, efforts, and external influences in order to make an actual investment. The purpose of this study determined the effect of accounting competencies, financial literacy, perceptive considerations, personality traits, and subjective stock market factors on the investment behavior as mediated by investment intention among Certified Public Accountants (CPA) in the Philippines. This study is derived on existing theories such as the theory of planned behavior, big five personality theory, perceived risk theory, and social cognitive theory. The methodology used, among others, were confirmatory analysis and quantitative methods using regression analysis which is expressed by variables such as (1) accounting competencies, (2) financial literacy, (3) perceptive considerations, (4) personality traits, and (5) subjective stock market factors, along with the primary data conducted during 2nd-3rd quarter of 2020 among CPA board passers from 2009 to 2019. Moreover, it used Partial Lease Squares – Structural Equation Model (PLS-SEM) analysis using SmartPLS statistical software. The study showed significant effect of financial literacy on investment behavior, and the effect of investment intention on investment behavior was also significant. Indirect effects showed no significant result.